Generalized order statistics from Kumaraswamy distribution and its characterization - Kumar, Devendra
We give explicit expressions and some recurrence relations for single and product moments of generalized order statistics from Kumaraswamy distribution. The results include as particular cases the above relations for moments of reversed order statistics and records. Further, using a recurrence relation for single moments we obtain characterization of Kumaraswamy distribution.
Keywords: Generalized order statistics; Kumaraswamy distribution and characterization